Emerging Coproduction of AmpC Beta-lactamase in Extended-spectrum Beta-lactamase-producing Escherichia coli Clinical Isolates in Indonesia - Mohammad Agung Marzah; Rosantia Sarassari; Dodi Safari; Yustinus Maladan; Wahyu Setyarini; Hanif Ardiansyah Sulistya; Pepy Dwi Endraswari; Toshiro Shirakawa; Itaru Hirai; Kuntaman Kuntaman; Eko Budi Koendhori (Wolters Kluwer - Medknow Publications, 2024)
Introduction: Extended-spectrum beta-lactamase (ESBL) and AmpC beta-lactamase (AmpC-BL) in Enterobacteriaceae are a global threat. Coproduction of AmpC-BL and ESBL reduces therapeutic options, with more resistance against cephamycin and beta-lactamase inhibitor combinations. This study determines the proportion, incidence, and distribution of AmpC-BL-resistant genes in clinically isolated ESBL-producing Escherichia coli, completing its scarce data in Indonesia. Methods: The samples in this study were ESBL-producing E. coli from blood and urine specimens, confirmed by BD Phoenix semiautomatic examination combined with cefoxitin disk screening method. Confirmation tests of AmpC-BL used the AmpC-disk method and the polymerase chain reaction method. Results: Thirteen (27.8%) of 108 E. coli isolates were nonsusceptible to cefoxitin, and 3 (11.5%) isolates were confirmed to produce AmpC-BL and contained AmpC-BL CITM gene. Of the 3 AmpC-BL and ESBL coproduction isolates, one isolate was a copresentation of ESBL and AmpC-BL genes, namely blaTEM and CITM. Fisher's exact test showed that the coproduction of AmpC-BL in ESBL-producing isolates was associated with reduced susceptibility to cefoxitin (P = 0.020) and amoxicillin-clavulanate (P = 0.048) compared to isolates producing ESBL alone. The effect of ESBL and AmpC-BL coproduction on reducing susceptibility to carbapenems needs further investigation. Conclusions: AmpC coproduction was found in 3 (2.8%) of 108 ESBL-producing E. coli isolates, and one isolate copresented AmpC-BL and ESBL coding genes blaTEM and CITM. These three isolates were associated with widened antibiotic resistance to cefoxitin and amoxicillin--clavulanate compared to isolates producing ESBL alone.